Multivariate-coupled-enhanced photoacoustic spectroscopy with Chebyshev rational fractional-order filtering algorithm for trace CH4 detection - Zha, Shenlong; Chen, Hang; Liu, Chen; Guo, Yuxiang; Ma, Hongliang; Zhang, Qilei; Li, Lingli; Zhan, Shengbao; Cheng, Gang; Cao, Yanan; Pan, Pan (Photoacoustics (Munich), 2025)
An innovative and miniature photoacoustic spectroscopy (PAS) gas sensor based on a multivariate-coupled amplification photoacoustic cell (MVCA-PAC) with a total length of 100 mm was developed to achieve ultra-sensitive trace CH4 detection. Acoustic pressure distribution simulations reveal that at the first-order resonance frequency, the MVCA-PAC achieves a maximum acoustic pressure approximately 3.9 times higher than that of a conventional photoacoustic cell. The absorption optical path of the MVCA-PAC reached 2068 mm through 22 reflections, resulting in a 2-fold increase in the amplitude of photoacoustic signals compared to the traditional photoacoustic cell with an equivalent absorption optical path. Furthermore, compared to a single-pass photoacoustic cell, the 2-f signal intensity of the MVCA-PAC increased by a factor of 4.5. Allan variance analysis indicated a detection limit of 0.572 ppm for CH4 detection with an averaging time of approximately 300 s. To further improve the measurement precision of the designed sensor, the Chebyshev rational fractional-order filtering (CRFOF) algorithm was introduced for PAS signal processing for the first time. Post-processing results demonstrated a 15.4-fold improvement in measurement precision, achieving a precision of 0.578 ppm. Finally, continuous monitoring of atmospheric CH4 over a 48-hour period validated the reliability and feasibility of the sensor.